2017
DOI: 10.3390/molecules22020248
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Composition and Antitumor Activity of Bee Bread Collected in Northeast Portugal

Abstract: Bee bread (BB) is a fermented mixture of plant pollen, honey, and bee saliva that worker bees use as food for larvae, and for young bees to produce royal jelly. In the present study, five BB samples, collected from Apis mellifera iberiensis hives located in different apiaries near Bragança, in the northeast region of Portugal, and one BB commercial sample were characterized by high-performance liquid chromatography coupled to a diode array detector and electrospray mass spectrometry (HPLC-DAD-ESI/MS) in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 17 publications
5
91
0
6
Order By: Relevance
“…1), the results show the presence of thirteen compounds, mainly flavonols glycoside derivative, especially quercetin, kaempferol, isorhamnetin, and methylherbacetrin derivatives. The identification of the phenolic compounds present were performed taking into account a previous study performed by Sobral et al (2017) using Portuguese bee bread samples, and the flavonol glycoside profile was very similar to the samples analyzed in that work. Of all the detected compounds isorhamnetin-O-hexosyl-O-rutinoside is the main phenolic compound present in this BB sample.…”
Section: Phenolic Compounds Profile Of Bee Breadmentioning
confidence: 99%
See 2 more Smart Citations
“…1), the results show the presence of thirteen compounds, mainly flavonols glycoside derivative, especially quercetin, kaempferol, isorhamnetin, and methylherbacetrin derivatives. The identification of the phenolic compounds present were performed taking into account a previous study performed by Sobral et al (2017) using Portuguese bee bread samples, and the flavonol glycoside profile was very similar to the samples analyzed in that work. Of all the detected compounds isorhamnetin-O-hexosyl-O-rutinoside is the main phenolic compound present in this BB sample.…”
Section: Phenolic Compounds Profile Of Bee Breadmentioning
confidence: 99%
“…In addition, they found that variables such as soil and climate do not appear to influence these compounds in the type of samples studied. Nevertheless, Sobral et al (2017) studied BB from different origins and detected differences in the phenolic composition of these samples. The antioxidant activity results (Table 4) revealed a total antioxidant capacity of 143 ± 22 mg equivalent of AA/g, the lower EC 50 was registered for the reducing power assay (EC 50 = 0.19 ± 0.03 mg/ mL), followed the ABTS assay (EC 50 = 0.50 ± 0.04 mg/mL), and DPPH assay (EC 50 = 0.98 ± 0.06 mg/mL).…”
Section: Phenolic Compounds Profile Of Bee Breadmentioning
confidence: 99%
See 1 more Smart Citation
“…Five BB samples were screened, using in vitro assays, against different human tumor cell lines, HeLa, HepG2, MCF-7, NCI-H460, and also against non-tumor liver cells (porcine liver cells, PLP2) [104]. From all the tested samples, BB3 was the only one to inhibit the growth of all tested cell lines, solely inhibiting the growth of HepG2.…”
Section: In Vitro Studies Of Bp and Bb Correlated To The Bioactive Comentioning
confidence: 99%
“…Bee bread may provide a significant amount of polyunsaturated fatty acids for the human body. Phytochemicals, such as flavonoid glycoside derivatives, widely exist in bee bread and have anticancer and antioxidant activities (Sobral et al, 2017). In the honeycomb, the conditions of fermentation process are quite complicated, and thus, producing bee bread by artificial simulations is difficult; however, it is technologically feasible to use BP as raw material by fermentation to obtain a nutraceutical for humans (Salazar-Gonz alez & D ıaz-Moreno, 2016).…”
Section: Introductionmentioning
confidence: 99%